Pemodelan Bawah Permukaan Daerah Vulkanik Jawa Tengah Berdasarkan Data Magnetik EMAG2-V3 - Herbianto, Sheren Aurellya; Rina Dwi Indriana; Muhammad Irham Nurwidiyanto (Jurnal Fisika Unand, 2025)
This study aims to analyze the subsurface magnetic properties of the volcanic region in Central Java based on EMAG2-V3 magnetic data. The magnetic data were reduced to the pole (RTP) to eliminate the effects of magnetic field inclination and declination, resulting in anomalies that are more symmetric with respect to their sources. Subsequently, magnetic anomaly separation was performed to obtain the regional and residual components. The resulting residual anomalies were further analyzed through two-dimensional inversion modeling to map the distribution of subsurface magnetic susceptibility. The interpretation results indicate that the residual magnetic anomalies range from -260 to 340 nT. Meanwhile, the inversion modeling reveals that subsurface susceptibility values vary from -10 × 10⁻⁴ to 20 × 10⁻⁴ CGS. Low susceptibility values are generally found in active volcanic bodies such as Mount Merapi, Merbabu, and Sumbing, indicating the presence of hydrothermal alteration zones and magma pockets. On the other hand, higher susceptibility values are mostly found on mountain slopes, associated with the presence of fresh volcanic rocks rich in ferromagnetic minerals. These findings suggest that magnetic anomaly analysis can be an effective method for revealing lithology and subsurface geological structures on a regional scale.